Право і буття : феноменологічний аспект праворозуміння - Козловський, Антон Антонович; Козловский, Антон Антонович; Kozlovskij, Anton (My University, 2012)
Being establishes a certain order of the world and is the law of being. Law and being are identical and non-law is nonbeing. Being is disclosing its law gradually before a man at the various levels which are interconnected. The law of being-in-itself is the law of the object world. The law of being-for-itself is the law of a man and the law of being-for-others is the law of people. If law is not directed to transcendence at each of the levels it tends to transform into nothing. The transcending mechanism is existence. Therefore the higher type of law is the existential one. Law as existence is the law of spirit and spiritual self-realization of human entity hence it is the real law of a man.
Козловський А. А. Право і буття : феноменологічний аспект праворозуміння / А. А. Козловський // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 203-215.
Keywords: онтологічні засади права; феноменологія права; екзистенціальне право; онтологические основания права; феноменология права; экзистенциальное право; ontological foundation of law; phenomenological law; existential law